On the Performance Analysis of Recursive Data Replication Scheme for File Sharing in Mobile Peer-to-Peer Devices Using the HyMIS Scheme - Mavromoustakis, Constandinos X.; Karatza, Helen D. (My University, 2006)
Advances in wireless networks enable high rates interaction between mobile devices. Short-range wireless communication technologies such as wearable PCs demand low latency and reliability as the first thing for considering QoS. Mobile Peer-to-Peer devices as an autonomous system of mobile routers that are selforganized, self-configured and completely decentralized are characterized by bounded resource sharing reliability. Due to the uncertainty in available resources wireless networks could rarely host file sharing applications in a reliable manner. This paper examines the response of a gossip-based data replication scheme for reliable file sharing under specified patterns and conditions, using the Hybrid Mobile Infostation System (HyMIS). This scheme is based on the advantages of mobile Infostations. Combining the strengths of autonomic gossiping and the hybrid –entirely mobile- Infostation concept, this scheme enables end to end reliability. Examination is performed for the response, the robustness and the offered reliability while examining the effectiveness of the proposed scheme for facing mobility limitations using the gossip-based ‘selection’ of users.